On the Selection of Queue Optimised Routing Protocol for VANET - Priya, Kanu; Malhotra, Jyoteesh (International Journal of Advanced Science and Technology, 2016)
VANET is one of the most escalating technologies that have been adopted due to its innovative applications and services. It has the potential to permit the vehicles on the roads to communicate intelligently in the absence of any fixed infrastructure. There are several challenges related to MAC and Routing Layer that needs attention for the intended implementation of VANET. Considering the challenge of optimisation of MAC Layer in VANET, work has been done here. The numerous Routing Protocols such as AODV, ADV, DSDV and GOD have been considered for the Cross layer Optimisation of 802.11b MAC Interface. The queue size has been optimised in terms of QoS parameters namely Throughput Rate, Packet Collision Rate, Packet Drop Rate and Broadcast Rate. The simulative investigations have been done for the aforementioned standard routing protocols by varying queue size and Optimised Routing Protocol for 802.11b MAC has also been identified.